Admission glycemic gap and other glycemic indices in assessing the need for mechanical ventilation among neurocritical patients with diabetes mellitus - Mazumder, Manas Kanti; Mozazfia, Kazi Tuba-E; Ahmed, Mostak; Abdul Hannan, Mohammad; Habibullah, AKM; Kumar Mondol, Montosh (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: We explored the value of admission glycemic gap (AGG) and other glycemic indices in determining the need for mechanical ventilation (MV) among neurocritical patients with diabetes mellitus. Methods: We purposively included 60 adult neurocritical patients with diabetes mellitus and prospectively studied them for 30 days, or until discharge or death. These patients stayed in the intensive care unit for at least 24 hours and did not require MV within the first twelve hours of admission. The glycemic indices included admission blood glucose level, A1c (HbA1c) level, A1c-derived admission glucose, A1c level, and AGG. The need for initiation of MV was determined according to standard institutional guidelines. Results: Among the 60 patients enrolled, 39 (65%) required MV. The need for MV was associated with female gender, ischemic stroke, history of insulin use, higher serum creatinine level, lower mean arterial pressure, higher AGG, admission blood glucose level, A1c, and A1c-derived admission glucose. A per unit rise of AGG (odds ratio (OR) 2.1; 95% confidence interval (CI) 1.4–3.1), and A1c (OR 2.6; 95% CI 1.2–5.4) had significant odds for the need for MV. AGG showed an optimal cut off value of 3.2 mmol/L, with a 79% and 81% sensitivity and specificity, respectively. The area under the curve was 0.79 (95% CI 0.66–0.91) for MV. Conclusion: Among neurocritical patients with diabetes mellitus, all of the evaluated glycemic indices affect the need for MV. The AGG cut-off of 3.2 mmol/L is an acceptable value to predict the need for MV.